Analisis Pengaruh Atas Pemahaman Riba Terhadap Menabung Di Bank Konvensional Bagi Para Mahasiswa UINSU - Efrida Rahma Sari Siregar; Adelia Hasibuan; Rizqa Amelia (Jurnal Manajemen Kreatif dan Inovasi, 2023)
Financial institutions appear in the economy when money has become a medium of exchange for buying and selling. Initially, this institution only served as a connecting vessel for buying and selling transactions. Then came the usury system. This study aims to determine whether the influence of student knowledge about usury can affect the intention to save in conventional banks at the State Islamic University of North Sumatra. The researcher uses a qualitative method with a descriptive approach in which the researcher uses field research by interviewing 10 informants, namely students at the State Islamic University of North Sumatra who have savings at conventional bank ATMs and Islamic banks. Because what we know is that students, especially UINSU students, must have learned about usury. However, in reality in the field, almost all student respondents definitely use conventional banks, which means they are indifferent to the law of usury. Therefore, the researchers concluded that students only need to learn more about usury and apply it to everyday life. Keywords: Financial institutions appear in the economy when money has become a medium of exchange for buying and selling. Initially, this institution only served as a connecting vessel for buying and selling transactions. Then came the usury system. This study aims to determine whether the influence of student knowledge about usury can affect the intention to save in conventional banks at the State Islamic University of North Sumatra. The researcher uses a qualitative method with a descriptive approach in which the researcher uses field research by interviewing 10 informants, namely students at the State Islamic University of North Sumatra who have savings at conventional bank ATMs and Islamic banks. Because what we know is that students, especially UINSU students, must have learned about usury. However, in reality in the field, almost all student respondents definitely use conventional banks, which means they are indifferent to the law of usury. Therefore, the researchers concluded that students only need to learn more about usury and apply it to everyday life.